Observer variation in detecting lymphadenopathy on chest radiography - Du Toit, Lionel George (Department of Paediatrics and Child Health, 2023)
Objective. To assess inter- and intra-observer agreement in the detection of lymphadcnopathy on chest radiography in children at risk for tuberculosis. Methods Dianostic test. Chest radiography using antero-posterior and lateral films. Observers. Four paediatric pulmonologists independently viewing the radiographs. Alain outcome measures. Inter- and intra-observer agreement on the presence or absence of lymphadenopathy, reported as present, absent or equivocal, and expressed as weighted Kappa statistics. Results. Weighted Kappa for the six pairs of observers ranged from 0.14 (95% Cl 0.02-0.30) to 0.52 (95% CT 0.35-0.69). After a 3-month interval intra-observer agreement ranged from 0.44 (95% Cl 0.25-0.62) to 0.71 (95% CI 0.56-0.87). Average weighted Kappa for inter-observer agreement was 0.33. Average intra-observer Kappa was 0.55. Conclusions. There was "fair" inter- and 'moderate" intra-observer agreement among paediatric pulmonulogists in detecting lymphadcnopathy on chest radiography in children. Caution is necessary when basing clinical decisions on the presence of lymphadenopathy on chest radiography.